2010
DOI: 10.1002/pts.913
|View full text |Cite
|
Sign up to set email alerts
|

Transport vibration laboratory simulation: On the necessity of multiaxis testing

Abstract: Nowadays, the packaging industry, like many other sectors, is coping with new demands resulting from fi nancial and environmental constraints. The importance of accurate laboratory simulation of transport vibration as a tool for packaging optimization is therefore increasing, as is highlighted by the International Safe Transit Association testing procedures (ISTA series). In this context, many studies can be found in the literature focusing on the special nature of transport vibrations, analysing the most suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 9 publications
1
36
2
5
Order By: Relevance
“…Then, a testing machine has to be able to analyse the dynamic behaviour of a load when all these directions are combined. In this sense, in [52] it is recommended the use of a 6 degree of freedom (DoF) shaking table, in addition to the simultaneous detection on a large number of points on trailer. The research showed, once more, that the real movements of the truck load bed during transport cannot be properly described with vertical acceleration alone.…”
Section: Laboratory Testmentioning
confidence: 99%
“…Then, a testing machine has to be able to analyse the dynamic behaviour of a load when all these directions are combined. In this sense, in [52] it is recommended the use of a 6 degree of freedom (DoF) shaking table, in addition to the simultaneous detection on a large number of points on trailer. The research showed, once more, that the real movements of the truck load bed during transport cannot be properly described with vertical acceleration alone.…”
Section: Laboratory Testmentioning
confidence: 99%
“…The effects of vertical restraint tension and stiffness were taken into account . Bernad et al investigated the dynamics of different corrugated stacked packaging units by means of operational modal analysis technique and a 6 degrees of freedom multi‐axis shaker table to demonstrate the necessity of multiaxis testing …”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, two publications compare the results of simulated uniaxial (heave) and multi‐axial vibrations of various packaging systems and identify important differences in the excitation of lateral mode shapes of staked packaging units and overall load stability. Attempts at evaluating the level and character of pitch and roll vibrations have been limited to a few observations .…”
Section: Introductionmentioning
confidence: 99%